Aspects of nutrition of the swordtail fish, Xiphophorus Helleri, (Family : Poeciliidae) under intensive culture conditions - Kruger, David Philip (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1996)
The aim of this work was to investigate the nutrition of a popular ornamental fish, the swordtail (Xiphophorus helleri), under intensive aquaculture conditions. The study focused on the formulation and manufacture of artificial dry diets, as well as the influence of livefeed supplementation on growth and nutritional indices of both juvenile and broodstock fish. A combination of 65% fishmeal and 35% soya oil cake meal was found to closely approximate the essential amino acid profile of X helleri (rÂ² = 94,3%) and lysine was identified as the first limiting amino acid. The influence of dietary protein and energy on the growth of X helleri was investigated by means of a growth trial comparing a range of nine test diets combining 3 crude protein (45,38 and 30%) and 3 digestible energy (16,5, 14,5 and 12,5 kJ/gram) levels. A high crude protein content (45% dry matter) and a protein to energy ratio of â‰¥ 27 mg protein per kJ digestible energy was shown to promote optimal growth rate and feed conversion ratio in juvenile X helleri. The final body protein and lipid content of the fish were significantly correlated with the dietary protein to energy ratio. The nutritional value of identical dietary formulations prepared by drum-drying or cold extrusion techniques and presented either as flake or crumble particles was evaluated in a growth trial and through analysis of vitamin C levels in the diets. Up to 27% of vitamin C activity was destroyed during the drum-drying of flake diets, while 80% of the remaining vitamin C was lost through leaching within 10 minutes of immersion in water. A crumble-type diet was shown to be acceptable to X helleri, and yielded significantly better growth rate and feed conversion than the equivalent flake feed. Almost 19% of fish fed the flake diets developed vitamin C deficiency symptoms including scoliosis and lordosis, while this was completely prevented by feeding crumbles, indicating a significant restriction of leaching losses from this type of particle. The use of livefeed (Daphnia spp.) as a daily supplement to dry feeds was shown to result in a significant improvement in growth rate and survival of juvenile swordtail fish. Furthermore, the synergistic action of nutrients contained in the livefeed resulted in an improvement in the feed conversion efficiency of the artificial formulation. While mortalities of 13,4% and 15% were recorded in fish fed exclusively on flake feed or Daphnia, no mortality occurred in the group fed the supplemented diet. Furthermore, the incidence of vitamin C deficiency symptoms was prevented by daily supplementation with Daphnia. Fish fed exclusively on Daphnia exhibited significantly more intense pigmentation due to carotenoids contained in the livefeed. In broodstock fish maintained primarily on flake diets, growth rate, feed conversion ratio as well as reproductive performance, as measured by fecundity, were significantly improved by daily livefeed supplementation. Weekly supplementation showed no measurable advantage over flake feed only. A direct correlation was demonstrated between fecundity and size of female fish with a mean fecundity of 190 embryos per female in those fed a daily Daphnia supplement. This was significantly higher than the yield from the non-supplemented or weekly supplemented treatments (133 and 140 embryos per female respectively). Despite these differences, the number of young harvested during the experiment did not differ between treatments and this discrepancy was ascribed to parental cannibalism of newborn juveniles. This phenomenon constitutes a major potential bottleneck in production with estimates of up to seventy percent of young lost in some exp experimental tanks. In conclusion, the present study demonstrated that established aquaculture nutrition principles and techniques are applicable to the tropical ornamental fish species, X helleri. It was demonstrated that by using balanced crumble feed formulations, and regular livefeed supplementation, production yields under intensive conditions may be significantly improved. Suggestions for future work on poeciliid production in South Africa include investigation of the economic implications of the recommendations stemming from this project, and further research into effective restriction of parental cannibalism of newborn fish.
Keywords: Xiphophorus helleri -- Nutrition; Fish culture